Pembinaan Health Habbit di Panti Asuhan Vania Anak Indonesia - Sani Susanti; Khodijah Tussolihin Dalimunthe; Brema Pardamean; Elena Agnesia; Rentaida Fellyesa; Siti Rahmadani; Tamara Adisa (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Health habbit development (healthy living habits) is healthy behavior that is carried out repeatedly without going through a thought process because this behavior is a response to something that is generally an everyday action. The aim of developing healthy habits is to improve the quality of life and individual well-being through implementing a healthy lifestyle. This coaching covers various aspects, such as a balanced diet, regular physical activity, adequate sleep, stress management and personal hygiene. This research examines how health habits are fostered at the Vania Anak Indonesia Orphanage Jln. Captain M. Jamil Lubis, Medan Estate, Deli Serdang, Deli Serdang Regency, North Sumatra 20371. The aim of this research is to find out what the healthy living habits of orphanage children at the Indonesian Vania Anak Orphanage are. This research uses a qualitative approach and a case study type of research. The subjects of the research were orphanage managers. This research data was collected using observation, interview and documentation techniques. Data is processed by data reduction, data presentation, as well as conclusions and verification. The results of the research show that the implementation of healthy living habits in Indonesian children's orphanages has not been implemented well, therefore the research team was present to provide guidance on health habits (Healthy Living Habits).